2014
DOI: 10.4028/www.scientific.net/amm.707.149
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Microalgae Protein Hydrolysates Prepared by Neutral Protease Digestion

Abstract: Microalgae protein hydrolysates (MPH) were obtained by enzymatic hydrolysis of defatted microalgae meal using neutral protease. The protein recovery, degree of hydrolysis, and the antioxidant activities of the hydrolysates were investigated. The results demonstrated that hydrolysates prepared by neutral protease at 50 °C for 4 h exhibited the strongest antioxidant activity. Under these conditions, the 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl radical scavenging activity and the reducing power of the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Bioactive peptides obtained after protein hydrolysis can have various beneficial effects. Hu et al [ 112 ] found that enzymatic hydrolysates of microalgae exhibit antioxidant properties. Chen et al [ 113 ] evaluated the hepatoprotective effect of the antioxidant peptide obtained by enzymatic hydrolysis from the microalgae Isochrysis Zhanjiangensis on alcohol damage to HepG2 cells.…”
Section: The Biological Activity Of Various Substances From Microamentioning
confidence: 99%
“…Bioactive peptides obtained after protein hydrolysis can have various beneficial effects. Hu et al [ 112 ] found that enzymatic hydrolysates of microalgae exhibit antioxidant properties. Chen et al [ 113 ] evaluated the hepatoprotective effect of the antioxidant peptide obtained by enzymatic hydrolysis from the microalgae Isochrysis Zhanjiangensis on alcohol damage to HepG2 cells.…”
Section: The Biological Activity Of Various Substances From Microamentioning
confidence: 99%
“…Peptides from protein hydrolysis have been studied due to their bioactivities. Some peptides have potential benefits such as antioxidative (Hu et al 2015), binding or inhibiting specific receptors (Kalpa W. Samarakoon et al 2014), growth factors, hormones, immunomodulators (de Jesus Raposo et al 2013, antihypertensive, anticoagulant and antiproliferative (Kalpa Samarakoon and Jeon 2012).…”
Section: Proteins and Peptidesmentioning
confidence: 99%
“…Protein hydrolysates from macro-and microalgae have been reported by various authors as possible therapeutic agents due to their antimicrobial and antiviral 3 , 4 , anticancer 5 , antioxidant 6 9 , and immunoregulatory functions 10 . Additionally, a close relationship has been observed between the antioxidant capacity of the protein hydrolysates and their hydrophobic and/or aromatic amino acid content 11 14 .…”
Section: Introductionmentioning
confidence: 99%